Enhancing Students' Explanatory Skills through the Implementation of STEM-Based Student Worksheets - Zulfa Rizka; Muhammad Syukri; Saminan Saminan; Siti Maghfirah; Elmi Mahzum; Lilia Ellany Mohtar (AL-ISHLAH: Jurnal Pendidikan, 2026)
Critical thinking skills, particularly scientific explanation abilities, remain inadequately developed among Indonesian secondary students, as evidenced by PISA 2023 results. While STEM-based learning shows promise for developing critical thinking, few studies have specifically examined its impact on the explanation indicator students' ability to construct coherent scientific arguments using claim-evidence-reasoning frameworks.  This study investigated whether STEM-based student worksheets (LKPD) incorporating the Engineering Design Process could improve students' explanation indicator scores in physics learning. A one-group pretest-posttest pre-experimental design was employed with 35 grade XI students at SMAN 2 Banda Aceh. Data were collected using a validated explanation ability test (covering claim-evidence-reasoning dimensions), student response questionnaires, and observation sheets aligned with Facione's critical thinking indicators. Paired samples t-test and N-Gain analysis were conducted to examine score changes. Pretest scores averaged 30.35±4.91%, while posttest scores reached 84.52±10.63% (t(34)=-27.427, p0.001, d=0.77, 95% CI [49.13, 59.21]). The N-Gain value of 0.77 indicated high improvement. Observation data showed explanation indicator performance at 89.2%, second only to self-regulation (97.14%). STEM-based LKPD was associated with substantial improvements in students' scientific explanation abilities. However, the one-group pretest-posttest design limits causal inferences; findings suggest correlation rather than definitive causation. The Engineering Design Process appears to provide structured opportunities for claim-evidence-reasoning practice essential for explanation development.